Frontal Sinus Malignancies: A Population‐Based Analysis of Incidence and Survival. (23rd December 2015) - Bhojwani, Amit; Unsal, Aykut; Dubal, Pariket M.; Echanique, Kristen A.; Baredes, Soly; Liu, James K; Eloy, Jean Anderson
Abstract : Objective: Primary neoplasms originating in the frontal sinus are rare. As such, existing literature describing frontal sinus malignancies (a subset of frontal sinus neoplasms) is limited. Prognostic implications of these malignancies are difficult to determine. This study seeks to analyze trends in epidemiology, clinicopathology, incidence, and survival for these rare malignancies. Study Design: Retrospective database analysis. Methods: The SEER 18 database (Surveillance, Epidemiology, and End Results; 1973‐2012) was searched for frontal sinus malignancies from 1973 to 2012 and analyzed for demographic and clinicopathologic trends. The Kaplan‐Meier model was utilized for survival analysis. Results: A total of 171 cases of frontal sinus malignancies were identified. Incidence was 0.011 per 100, 000 individuals. The mean age at diagnosis was 61.1 years, with males constituting the majority of cases (61.4%). 80.1% of patients were white, 9.4% Asian, and 8.2% black. The average tumor size was 3.8 cm. The most common histology encountered was squamous cell carcinoma (39.8%). Overall 5‐year disease‐specific survival was 44.2%. Five‐year disease‐specific survival was highest for mature B‐cell non‐Hodgkin's lymphomas (72.3%) and lowest for adenocarcinomas (15.4%). Conclusions: Malignant tumors of the frontal sinus are rare and are more common in males. Squamous cell carcinoma is the most common entity encountered. Of the 4 most common histologies, survival is best for mature B‐cell non‐Hodgkin's lymphomas and worst for adenocarcinomas.